2017
DOI: 10.7589/2017-01-011
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Detection of Subtype-specific Antibodies to Influenza A Viruses in Southern Sea Otters (Enhydra lutris nereis)

Abstract: There are approximately 3,000 southern sea otters (Enhydra lutris nereis) in the nearshore environment along the California coast, US, and the species is classified as Threatened under the Endangered Species Act. We tested sera from 661 necropsied southern sea otters sampled from 1997 to 2015 to determine overall exposure to influenza A viruses (IAVs) and to identify subtype-specific antibody responses. Using an enzyme-linked immunosorbent assay (ELISA), antibodies to IAV nucleoproteins were detected in 160 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Furthermore, several serosurveys have been performed on mink to look for the prevalence of anti-H9N2 antibodies, all three studies have shown a high seropositivity in farmed minks in China of between 20% and 45% [192,196,197]. Sea otters are also members of the family Mustelidae, a single serosurvey has found antibodies against H9 HA, however, this is perhaps unsurprising considering the presence of H9 viruses in seabirds and the relatively long lifespans of the otters [198].…”
Section: H9n2 Infection In Other Speciesmentioning
confidence: 99%
“…Furthermore, several serosurveys have been performed on mink to look for the prevalence of anti-H9N2 antibodies, all three studies have shown a high seropositivity in farmed minks in China of between 20% and 45% [192,196,197]. Sea otters are also members of the family Mustelidae, a single serosurvey has found antibodies against H9 HA, however, this is perhaps unsurprising considering the presence of H9 viruses in seabirds and the relatively long lifespans of the otters [198].…”
Section: H9n2 Infection In Other Speciesmentioning
confidence: 99%
“…Furthermore, several serosurveys have been performed on mink to look for the prevalence of anti-H9N2 antibodies, all three studies have shown a high seropositivity in farmed minks in China of between 20% and 45% [167,171,172]. Sea otters are also members of the family Mustelidae, a single serosurvey has found antibodies against H9 HA, however this is perhaps unsurprising considering the presence of H9 viruses in seabirds and the relatively long lifespans of the otters [173].…”
Section: Mustelidaementioning
confidence: 99%
“…BJ94like H9N2 viruses have been reported from minks in China, some of which carry the E627K mutation in PB2 associated with mammalian adaptation (Subbarao et al 1993;Hatta et al 2001;Peng et al 2015). Serological studies in sea otters (also in the Mustelidae family) revealed antibodies to H9 viruses, perhaps resulting from exposure to H9 IAVs carried by sea birds (Capuano et al 2017).…”
Section: Clinical Signs Pathology and Interspecies Transmissionmentioning
confidence: 99%